Ugoda administracyjna i postanowienie o zatwierdzeniu/odmowie zatwierdzenia ugody: [Administrative settlement and resolution on approval/refusal of approval of settlement] (Studia Prawnicze / The Legal Studies, 2011)
Celem artykułu jest omówienie dwóch instytucji prawa administracyjnego proceduralnego: ugody administracyjnej i postanowienia o zatwierdzeniu lub odmowie zatwierdzenia ugody. Przedmiotem badania będą konstrukcje prawne obu tych instytucji i relacje pomiędzy nimi. W doktrynie prawa administracyjnego relacja ugody administracyjnej i postanowienia o zatwierdzeniu ugody nie jest jednolicie interpretowana. Przeważający pogląd uznaje dwuczłonową koncepcję budowy ugody administracyjnej, na którą składa się porozumienie stron oraz postanowienie o zatwierdzeniu ugody; dopiero oba te elementy łącznie uznawane są za ugodę administracyjną.Odmienny pogląd głosi, że właściwą ugodą jest postanowienie o zatwierdzeniu ugody wywołujące skutki materialnoprawne. W świetle tej koncepcji zbędne jest wymienianie ugody jako osobnej prawnej formy działania administracji. Właściwą prawną formą działania administracji jest postanowienie o zatwierdzeniu ugody, które wydane zostaje w szczególnym trybie i wywołuje skutki materialnoprawne na równi z decyzją administracyjną. The purpose of this article is to present the institution of administrative procedural law, the administrative settlement, regulated under Chapter 8 of the Administrative Procedure Code (APC). The conditions of admissibility of the settlement, the mode of its preparation, inspection and approval have been discussed. In context of the introduced classification of procedural facts, there have been made a detailed procedural analysis of procedural actions of the parties and administration authority in the procedure of conclusion, preparation and approval of the settlement. In relation to the views of doctrine and jurisprudence the author examines the normative construction of settlement in the APC. The view prevailing in the doctrine considers administrative settlement as an agreement concluded by the parties and approved by the administration authority (so-called binary construction of administrative settlement). Recognizing this view as erroneous the author shows that, from the procedural point of view, the settlement is constituted solely by the agreement concluded by the parties, prepared by the administration authority and signed by an authorized officer of the administration authority and by the parties. Defined in such way, the administrative settlement is a non-imperial legal form of action of administration- the actual action consisting of preparing the settlement and signing it by an authorized officer. Unapproved administrative settlement has the procedural effects such as the obligation of inspection and obligation to issue a resolution on its approval (refusal of approval). Approval (refusal of approval) of the administrative settlement, in the form of resolution, is a separate legal form of action of administration, the unilateral imperial declaration of will, the administrative act.